2019
DOI: 10.1364/oe.27.007822
|View full text |Cite
|
Sign up to set email alerts
|

Memory-controlled deep LSTM neural network post-equalizer used in high-speed PAM VLC system

Abstract: Linear and nonlinear impairments severely limit the transmission performance of high-speed visible light communication systems. Neural network-based equalizers have been applied to optical communication systems, which enables significantly improved system performance, such as transmission data rate and distance. In this paper, a memory-controlled deep long short-term memory (LSTM) neural network post-equalizer is proposed to mitigate both linear and nonlinear impairments in pulse amplitude modulation (PAM) bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Note that it is reasonable to assume a 20-MHz modulation bandwidth in the simulations, since various FDE schemes can be applied to extend the limited 3-dB modulation bandwidth of COTS white LEDs [11]- [13]. Moreover, by regulating the input signal within the dynamic range of the LED and applying various LED nonlinearity compensation techniques such as pre-or post-distortion and post-equalization [40]- [44], it is also reasonable to neglect the nonlinear effects of the LED in the simulations.…”
Section: Analytical and Simulation Resultsmentioning
confidence: 99%
“…Note that it is reasonable to assume a 20-MHz modulation bandwidth in the simulations, since various FDE schemes can be applied to extend the limited 3-dB modulation bandwidth of COTS white LEDs [11]- [13]. Moreover, by regulating the input signal within the dynamic range of the LED and applying various LED nonlinearity compensation techniques such as pre-or post-distortion and post-equalization [40]- [44], it is also reasonable to neglect the nonlinear effects of the LED in the simulations.…”
Section: Analytical and Simulation Resultsmentioning
confidence: 99%
“…Note, the boundaries have a high dependency on the number of neurons and the hidden layers, which are analogous to the human brain, where the synaptic weight is changed based on the training sequence. Different ANN approaches can be deployed for equalisation including the single-layer [33] and the multi-layer perceptron (MLP) [31]. In [26] it was shown that, MLP offers superior performance in mitigating ISI in optical wireless systems and hence, has been adopted in this work.…”
Section: Artificial Neural Network Equalisermentioning
confidence: 99%
“…In recent years, machine learning especially neural network (NN) has become very popular and been introduced in optical communications for monitoring the optical signal to noise ratio (OSNR) [14], modulation format recognition [14], nonlinearity mitigation [15] and CE [16][17], etc. In [16], the NN-based equalizer was used to mitigate both linear and nonlinear distortion in a 100 Gb/s PON system.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], the NN-based equalizer was used to mitigate both linear and nonlinear distortion in a 100 Gb/s PON system. In [17], a memory controlled deep long short-term memory (LSTM) NN-based post-equalizer was proposed to mitigate the transmission impairment in pulse amplitude modulation VLC systems. In [18], a LSTM network was proposed to detect the channel characteristics automatically for a typical NOMA system.…”
Section: Introductionmentioning
confidence: 99%